Detection of insect's meal in compound feed by Near Infrared spectral imaging. (30th November 2018) - Mandrile, Luisa; Fusaro, Ilaria; Amato, Giuseppina; Marchis, Daniela; Martra, Gianmario; Rossi, Andrea Mario
Highlights: An innovative method to detect and quantify insect meal in feed is proposed. The proposed method represents a valuable tool for developing feed legislation. Near Infrared Imaging is suitable for the detection of insects' meal in feed. Linear Discriminant Analysis it used to identify insect's fragments in NIR images. Automatic and non-operator dependent recognition of insects' meal is achieved. Abstract: Insects have recently emerged as a new protein source for both food and feed. Some studies have already demonstrated that insects' meal can be successfully added to animal feed without threaten animals' growth indices. However, effective and validated tests to individuate insects' meal in feed are strongly needed to meet traceability and safety concerns and to support the European legislation under development. Spectroscopic techniques represent valuable rapid and non-destructive methods that can be applied for in-situ analysis in feed production plants or in farms. In this work a Fourier Transform Near Infrared spectroscopy imaging (FT NIR) as a potential screening method for the detection and quantification of insects' meal in feed is presented. Discriminant analysis was used for the automatic recognition of insects' meal fragments into the feed matrix. Moreover, the possibility to quantify insect's meal in feed sample was successfully tested. The proposed method is a rapid and green strategy for feed contamination screening analysis.